Architecting Digital Transformation: A Framework for Legacy Modernization Using Microservices and Integration Platforms - Rajalingam Malaiyalan, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
In an increasingly digital and data-driven environment, modernising old systems is essential for businesses looking to improve operational efficiency, scalability, and security. Innovation and long-term sustainability are seriously hampered by traditional infrastructures, which are weighed down by technological debt, security flaws, and operational inefficiencies. A scalable strategy to modernising historical systems is examined in this research, with a focus on next-generation data structures and smooth integration techniques. It looks at the shortcomings of antiquated systems, the advantages of distributed and cloud-native designs, and how microservices and event-driven frameworks may increase system agility. This abstract examines how software architecture has changed in the modern period, emphasising important developments and problems that architects encounter. It examines at how established architectural concepts are being reinterpreted to satisfy the needs of cutting-edge technologies like artificial intelligence, cloud computing, microservices, and the Internet of Things (IoT). Case studies show how effective change management and phased techniques may result in significant long-term advantages including lower technical debt, more scalability, and increased flexibility to accommodate new developments. The report concludes with predictions for future developments, including low-code/no-code accelerators and AI-enabled refactoring, highlighting how successful modernisation not only protects mission-critical operations but also lays the groundwork for long-term organisational growth and digital transformation.
Keywords: Modernizing Legacy; Event-Driven Frameworks; Operational Efficiency; Cloud-Native; Internet of Things; Improved Scalability; Data Architectures; AI-Enabled; Cloud Computing; Software Architecture